KEMAMPUAN PENALARAN MATEMATIS SISWA PADA PEMBELAJARAN TAI (TEAM ASSISTED INDIVIDUALITION) DENGAN PENDEKATAM SAINTIFIK - Laurensia Dhika Maretasani (Universitas Katolik Widya Mandala Surabaya Kampus Kota Madiun, 2017)
The purpose of this study were (1) determining the students mathematical reasoning ability by TAl scientific approach learning, (2) examining the student mathematical reasoning ability among the TAI scientific approach learning better than the student mathematical reasoning ability among the expository learning. The population in this research was the 8th grade all of students from one of Junior High School at Sragen. The sample of this program was taking by cluster random sampling technic. The data obtained through of test. The data analyzing of students mathematical reasoning ability include test for normality using Kolmogorov-Smirnov test, proportion test, One Way Anova test, and further tests with LSD. The conclusions obtained were (1) mathematical reasoning abilities of students with TAI thoroughly scientific approach learning reached 89%, (2) the students mathematical reasoning abilities with TAI scientific approach learning (81.48) was better than the students mathematical reasoning abilities with expository learning (69.04).